Visualization of oxidative injury in the mouse kidney using selective superoxide anion fluorescent probes - Lv, Yun; Dan Cheng, Dan Cheng; Dongdong Su, Dongdong Su; Chen, Mei; Yin, Bin-Cheng; Yuan, Lin; Zhang, Xiao-Bing (Chemical science (Cambridge), 2018)
Drug-induced acute kidney injury (AKI), caused by renal drug metabolism, has been regarded as a main problem in clinical pharmacology and practice. However, due to the lack of effective biomarkers and noninvasive real-time tools, the early diagnosis of drug-induced AKI is still a crucial challenge. The superoxide anion (O 2 ˙ − ), the preliminary reactive oxidative species, is closely related to drug-induced AKI. In this paper, we reported two new mitochondria-targeted fluorescent probes for investigating AKI via mapping the fluctuation of O 2 ˙ − with high sensitivity and selectivity by the combination of rational design and a probe-screening approach. Small-molecule fluorescent probes ( Naph-O2˙− and NIR-O2˙− ) with high accuracy and excellent selectivity were successfully applied to detect endogenously produced O 2 ˙ − in living cells and tissues by dual-model confocal imaging, and to trap the fluctuation of the O 2 ˙ − level during the drug-induced nephrotoxicity. Moreover, probe NIR-O2˙− was also used to elucidate the protective effects of l -carnitine (LC) against drug-induced nephrotoxicity for the first time. Therefore, these probes may be potential chemical tools for exploring the roles of O 2 ˙ − in complex nephrotoxicity disease systems.